Cadaveric Study and Micro-Computed Tomography of the Anatomy of Palatine Aponeurosis and its Link to the Soft Palate Muscles and Pharyngeal Muscles. (March 2023) - Zhao, Jiuli; Ma, Hengyuan; Wang, Yongqian; Song, Tao; Wu, Di; Yin, Ningbei
Objective: There have been few studies on the anatomy of palatine aponeurosis (PA). Herein, we elucidated the relationship between the PA and soft palate muscles and pharyngeal muscles. Design: Two cadaveric specimens were dissected to observe the gross anatomy of the PA. Six cadaveric specimens were processed and scanned by micro-computed tomography to determine the elaborate anatomy. Images were exported to Mimics software to reconstruct a three-dimensional model. Results: The PA covered the anterior (32.1%-38.8%) of the soft palate, extending from the tensor veli palatini (TVP) and connecting to 3 muscles: palatopharyngeus (PP), uvula muscle, and superior pharyngeal constrictor (SC). The SC and PP are attached to the PA on the medial side of the pterygoid hamulus. SC muscle fibers were attached to the hamulus, forming a distinct gap between the hamulus. Some muscle fibers of the PP and uvula originated from the PA. The PA extended from the TVP to the midline and the posterior edge of the hard palate. The PA was not uniformly distributed, which was complementary to the attached muscles in thickness. Conclusions: PA, as a flexible fibrous membrane, maintains the shape of the soft palate. It extends from the TVP and covers anteriorly about one-third of the soft palate. The PA provides a platform for the soft palate muscles and pharyngeal muscles, connecting to the PP, uvula muscle, and SC. These muscles are important for palatopharyngeal closure and middle-ear function. It is necessary to minimize the damage to the PA during surgical interventions.